138k views
5 votes
Select the correct answer from the drop down menu

Select the correct answer from the drop down menu-example-1
User Marjer
by
4.8k points

1 Answer

1 vote


((f)/(g))(x)=(x^(2) +2x-3)/(x^2-9) since x = 4, you plug in 4 into the x's in the equation


((f)/(g) )(4)=((4)^2+2(4)-3)/((4)^2-9) = (16 + 8 - 3)/(16 - 9) Simplify


(21)/(7) =3

so
((f)/(g))(4)=3

(f + g)(x) = (x² + 2x - 3) + (x² - 9) Plug in 4 for x

(f + g)(4) = 4² + 2(4) - 3 + (4)² - 9

(f + g)(4) = 16 + 8 - 3 + 16 - 9 = 28

User Tommasop
by
5.5k points